Security Consolidation in the Aftermath of Civil War: Explaining the Fates of Victorious Militias. (October 2021) - Bolte, Brandon; Joo, Minnie M.; Mukherjee, Bumba
Policymakers and peacebuilding research often focus on rebel groups when studying demobilization and integration processes, but post-war governments must also manage the non-state militias that helped them gain or maintain power. Why do some post-war governments disintegrate their militia allies, while others integrate them into the military? We argue that when a salient ethnic difference exists between the (new) ruling elite and an allied militia, a process of mutual uncertainty in the post-war period will incentivize governments to disintegrate the group. However, governments will be most likely to integrate their militias when the military has sufficient coercive capabilities but few organizational hindrances to re-organizing. Using new data on the post-war fates of victorious militias across all civil conflicts from 1989 to 2014, we find robust support for these claims. The results suggest that a government's optimal militia management strategy is shaped by both social and organizational constraints during the post-war period.